Effectiveness of Copper Desorption from Activated Carbon Using Variations of Acid Solution Concentration - Maharani, Regita; Mirwan, Mohamad; Zakiyayasin Nisa’, Syadzadhiya Qothrunada (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The presence of heavy metals, such as copper (Cu²?), in industrial wastewater poses environmental problems due to their toxicity and resistance to natural degradation. One of the treatment methods used is adsorption with activated carbon, which has a high surface area and porosity. However, the adsorption capacity decreases after several cycles of use, necessitating regeneration via desorption. This study aims to determine the effectiveness of Cu²? ion desorption from activated carbon using various concentrations of HCl solution and to analyze morphological changes in the adsorbent after desorption. The desorption experiments were carried out with HCl concentrations of 0.05 M, 0.1 M, 0.15 M, 0.2 M, and 0.25 M, and with contact times of 30, 60, 90, and 120 minutes. The Cu ion concentration was analyzed using an Atomic Absorption Spectrophotometer (AAS), and the surface morphology was characterized using a SEM. The outcomes showed that increasing the HCl concentration enhanced desorption efficiency, reaching a maximum of 49.9% at 0.25 M, with an optimum contact time of 90 minutes. SEM analysis revealed changes in the pore structure and surface morphology of the activated carbon after desorption, indicating the release of metal ions from the adsorbent surface. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production